KOSTNAYa MASSA I KOSTNYY METABOLIZM U DETEY S YuVENIL'NYM IDIOPATIChESKIM ARTRITOM - M. M. KOSTIK; M. M. MNUSKINA; I N MAKAROVA; D. A. KUZ'MINA; L. A. ShchEPLYaGINA; V. I. LARIONOVA (Остеопороз и остеопатии, 2011)
This study describes bone metabolism in children withjuvenile idiopathic arthritis (JIA), association between disturbances of bone metabolism with inflammatory activity, juvenile arthritis disease course and therapy in 198 children. Low bone mineral density (BMD) for chronological age was detected by dual-energy X-ray absorptiometry of lumbar spine L1-L4 (densitometer Hologic QDR 4500C, with pediatric reference database) than Z -score < -2 SD in 36 children (18,2%), in 18 girls (15,5%) and in 18 boys (21,9%). Girls with low BMD received glucocorticoids (GCS) in 66,7 % cases, and girls with normal BMD received it in 26,5% cases (р=0,002). Girls with low BMD had lower height, weight, earlier age of disease onset and higher clinical and laboratory parameters of arthritis activity. Girls with low BMD had higher osteocalcin and tendency to decreased parathyroid hormone levels compared to the girls with normal BMD. Children who received GCS had specific stereotypic changes: boys had significantly lower bone mineral density and total Ca and girls had significantly lower bone mineral content and BMD (g/cm2 and Z-score), total Са, non-organic phosphate and total alkaline phosphatase activity. Patients with systemic arthritis had significantly lower mineralization and bone metabolism turnover compared to children with oligoarticular and polyarticular JIA subtypes. Independent predictors of skeletal mineralization were age onset f JIA (р<0,0001), duration of the disease (p<0,0001), hemoglobin level (р=0,004), total calcium level (р=0,024), a2-globulins level (р=0,046). Independent predictors of low BMD were physician’s assessment VAS (р=0,024), C-reactive protein (р=0,04), inorganic phosphate (р=0,05). Systemic glucocorticoids exposure elevated the risk of low BMD for chronological age realization in JIA patients (OR=1,96, 95%CI=0,76-5,05). Enhanced risk of low BMD was in polyarthicular (OR=2,53, 95%CI=0,66-9,65) and systemic JIA (OR=3,16, 95%CI=0,73-13,76). Thus, parameters of inflammation have negative influence on bone metabolism velocity, linear growth and accordingly bone mineralization. Described factors explain heterogeneity of mineralization disorders.